Technical Parameters of In Vivo Red Blood Cell Labeling with Technetium-99m - Zimmer, A. M.; Pavel, D. G.; Karesh, S. M. (Nuklearmedizin - NuclearMedicine, 1979)
The in vivo labeling of red blood cells (RBC) using sequential injections of stannous pyrophosphate and 99mTc-pertech- netate has resulted in excellent blood pool images since it was initiated in our laboratory in 1975. Recently certain technical parameters of the procedure have been further researched and clarified. The optimum RBC labeling has been obtained by using 1.43 mg “cold” Sn-PYP/1000 ml blood and a 30-minute lag time prior to pertechnetate injection (15-20 mCi). The binding of 99mTc to RBCs is not instantaneous, but requires several minutes for completion. The “secondary” RBC labeling effect of additional pertechnetate, added after the initial in vivo labeling, demonstrates an initial rapid fall in the labeling efficiency as a function of time followed by a more gradual decrease; the level of baseline (spontaneous) RBC labeling is achieved approximately 8 days after an initial in vivo labeling. Monitoring in vivo RBC labeling over several hours indicates that more than 90 % of the initial activity was still in the vascular blood pool at 4 hours, bound to RBCs.